Research And Development at "Dharmaisâ Cancer Center Hospital (National Cancer Center) - A new Paradigm for National Cancer Control Program in Indonesia - DWIPOYONO, BAMBANG (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43609509/Research-And-Development-at-Dharmais-Cancer-Center-Hospital-National-Cancer-Center-A-new-Paradigm-for-National-Cancer-Control-Program-in-Indones